ANALISIS FITUR LAYANAN DAN KEAMANAN TERHADAP PENGGUNAAN DOMPET DIGITAL (SHOPEE PAY) - Wawan Setiawan; Dede Sunaryo; Khorida AR (Digital Business Journal, 2022)
AbstractThe purpose of this study was to determine the effect of service and security features on the use of digital wallets (Shopee Pay) on SMEs in Tangerang City. This study uses a quantitative approach. The population in this study is SMEs in Tangerang City that use Digital Wallets, the number of which is not known with certainty. The sampling formula used was the Lemeshow formula and obtained a sample size of 96. The data analysis technique used was multiple linear regression. The results of the study show that (1) Service Features have a positive and significant effect on Digital Wallet Usage, as evidenced by the value of tCount > tTable (4.178 > 1.661) with a significance (0.000 <0.05). (2) Security has a positive and significant effect on the use of Digital Wallets, as evidenced by the value of tCount > tTable (2.331 > 1.661) with a significance (0.000 <0.05). Service and Security Features affect the Use of Digital Wallets by 47.3%, the remaining 52.7% is influenced by other variables.Keywords: Use of Digital Wallets, Service Features, and Security.